analisis Roland Barthes Analisis Semiotika Roland Barthes pada Prosesi Pernikahan Adat Sunda "Sawer Pengantin": Analisis Semiotika Roland Barthes pada Prosesi Pernikahan Adat Sunda "Sawer Pengantin" - Aida Nuraida Aida (Jurnal Bimas Islam, 2023)
The uniqueness of Indonesian culture, one of which can be seen when holding a traditional ceremony, Of the many cultures in Indonesia, one of the customs that is often used in weddings is the Sundanese custom. Indeed, the main moment awaited in a marriage is the procession of the ijab. But the traditional procession is also one of the solemn moments in a wedding. The Sundanese traditional wedding series that is often used by brides is "sawer penganten. sawer penganten series contains several other events, such as nyawer, meuleum harupat, nincak endog, open the door, huap lingkung, pabetot bakakak hayam, and ngaleupaskan japati. So, in this study, the author relates the meaning for the sake of meaning from a series of events to Rolland Barthes' semiotic theory of denotation, connotation, and mythical elements. The type of research taken is qualitative, relying on several book references and interviews with several traditional experts to obtain valid and reliable data. Based on the results of the research, it shows that a series of "sawer penganten" ceremonies are more inclined to the elements of belief expressed in the form of figurative meanings and symbols of events. Everything done by the bride and groom and their parents in the sawer penganten activity contains prayers and hopes for a better life for the bride and groom. In fact, it also contains prayers for everyone who is present and joins in praying for the bride and groom so that all those present get blessings from God through the ceremony. In addition, it also contains a lot of advice and provisions for life for all who witness it, especially for the bride and groom as they carry out married life. Everything is carried out in accordance with the laws and regulations of the religion that is fully embraced. Thus, the traditional Sundanese wedding ceremony is a combination of elements of nature, characteristics, beliefs, and religion, all of which support each other so as to create a virtuous human being.